Behavior of Family in Practice Hepatitis B Immunization at Baby 0-7 Days Old - Kusnanto Kusnanto; Elida Ulfiana; M. Hadarani (Jurnal Ners, 2008)
Introduction: Result of coverage hepatitis B immunization  at 0-7 days old babies in Puskesmas Banjarbaru Banjarbaru city South Kalimantan until year 2008 was under 40%. The cause of unsuccessfully of giving hepatitis B immunization  at 0-7 days old babies was the behavior of the family. This research aimed to explain family behavior in execution immunization at 0-7 days old babies in region of Puskesmas Banjarbaru. Method: The design used in this research was analytic design. total sample were 30 respondents. Variable in this research were behavior of family in practice hepatitis B immunization  at baby 0-7 days old, which covers  knowledge, attitude and practice in hepatitis B immunization  at baby 0-7 day old. The data was collected by questionnaire and analyzed by using statistical test chi-square with level of significance α≤0.05. Result: The result showed a correlation between knowledge and attitude about hepatitis B immunization  at 0-7 days old babies (x2=0.000). Discussion: There was correlation between knowledge and hepatitis B immunization performed by the family to the  baby ages  0-7 days old (x2=0.015). A correlation between attitude with family practice with giving hepatitis B immunization  at baby ages 0-7 days old (x2=0.000).